IMPLEMENTING KWL STRATEGY TO IMPROVE READING COMPREHENSION OF RECOUNT TEXT IN VOCATIONAL SCHOOL LEVEL - Ni Ketut Asta Denny Sadewi; I Ketut Wardana; Komang Budiari (International Journal of Instructions and Language Studies, 2025)
Using the Classroom Action Research (CAR) approach, the main objective of this research was to ascertain whether the KWL strategy could improve students' reading comprehension of recount texts. 36 students from SMK Negeri 5 Denpasar's class X PH 3 were chosen at random to take part in the research. Questionnaires were used as secondary data for this study, while pre-test and post-test data were gathered as main data. The results indicated that only 4 students (11.11%) scored above the passing grade in the pre-test, while 32 students (88.89%) scored below it. Following the implementation of the KWL method in Cycle 1, the results of Post-Test 1 showed improvement, with 19 students (52.78%) achieving scores above the passing grade. Further progress was noted in Cycle 2, where 26 students (72.22%) scored above the passing grade. The mean score difference was 19.58 points between the pre-test and Post-Test 1, and 4.59 points between Post-Test 1 and Post-Test 2. These findings suggest that students’ reading comprehension of recount texts can be enhanced through the KWL method. Additionally, the results of the questionnaire indicated that most students felt the strategy was implemented effectively. They believed that the KWL strategy improved their understanding of the text’s main ideas, factual details, vocabulary, linguistic elements, text structure, and social functions. Furthermore, this strategy increased students’ reading motivation and self-esteem. Therefore, the KWL strategy proved to be a valuable approach for teaching reading comprehension, particularly about recount texts. Keywords: KWL Strategy, Reading Comprehension, Recount Text.